2021
DOI: 10.3390/lubricants9050046
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Behavior of Graphene and Ionic Liquid as Bio-Based Lubricant Additive

Abstract: The constant utilization of petroleum-based products has prompted concerns about the environment, hence a replacement for these products must be explored. Biolubricants are a suitable replacement for petroleum-based lubricants as they provide better lubricity. Biolubricant performance can be improved by the addition of graphene. However, there are reports that graphene is unable to form a stable suspension for a long period. This study used a graphene-ionic liquid additive combination to stabilize the dispersi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…ILs can be added into other lubricants as additives to reduce coefficient of friction (COF) and wear rate [12], such as bio-based lubricant [13], water-based lubricants [14], and oil-based lubricants [15], even at relatively high temperature [16]. ILs can increase the stability of lubricant additives [16], such as NiAl particles and trihexyl(tetradecyl)phosphonium cation [17], and improve their tribological performance.…”
Section: Ionic Liquid Lubricationmentioning
confidence: 99%
“…ILs can be added into other lubricants as additives to reduce coefficient of friction (COF) and wear rate [12], such as bio-based lubricant [13], water-based lubricants [14], and oil-based lubricants [15], even at relatively high temperature [16]. ILs can increase the stability of lubricant additives [16], such as NiAl particles and trihexyl(tetradecyl)phosphonium cation [17], and improve their tribological performance.…”
Section: Ionic Liquid Lubricationmentioning
confidence: 99%
“…182 In other studies, mixing ILs with allotropes of carbon like graphene has shown great potential in biolubricants formulation. For example, Hasnul et al, 183 utilized graphene and ionic liquid additives in biolubricants to improve the biolubricants tribological performances. This is because graphene oxide can form a stable colloidal suspension without using surfactant in pure ionic liquid.…”
Section: Tribological Performance Of Biolubricantsmentioning
confidence: 99%
“…Engine oil is crucial in automobiles to prevent heat and corrosion due to friction. Several studies 1–37 explored the commercial use of biobased oils. Ting and Chen 34 proposed the possibility of producing new lubricants with esters from seed oils, thus minimizing toxicity and improving the biodegradability of engine oils over time.…”
Section: Introductionmentioning
confidence: 99%